Cultivating Racial Diversity or Reproducing Whiteness?: A QuantCrit Analysis of School Districts' Early Principal Hiring Practices. Issue 1 (2nd January 2022) - Reynolds, Amy Luelle; Tabron, Lolita A.
ABSTRACT: The purpose of our study was to illuminate patterns in district early principal hiring practices (EPHPs) that suppress, reproduce, or build equity and diversity in the principalship. Using Quantitative Criticalism as a framework, we found that district EPHPs do not disrupt longstanding patterns of inequity and exclusion. Instead, the practices perpetuate the reproduction of Whiteness in the principal pipeline. We illustrate ways district leaders' actions and inactions in EPHPs reproduce or disrupt historical patterns of BIPOC exclusion from the principalship.